2017
DOI: 10.1007/s12599-017-0501-5
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Informed Decision-Making in Financial Service Encounters

Abstract: While advice-giving

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…From a more technical perspective, Faloon and Scherer (2017) identified personalization as the distinctive feature of robo-advisors compared to traditional human advisory services. In turn, Heinrich and Schwabe (2018) concluded that IT-supported advice-giving processes increase customers’ learning, enabling them to make more informed decision related to financial products.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From a more technical perspective, Faloon and Scherer (2017) identified personalization as the distinctive feature of robo-advisors compared to traditional human advisory services. In turn, Heinrich and Schwabe (2018) concluded that IT-supported advice-giving processes increase customers’ learning, enabling them to make more informed decision related to financial products.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, the methodology used in this research has focused on design of an IS system/prototype (''artifact'') using two components, namely clustering and ATS, as the first step, followed by evaluation of its ''utility''. Essentially, the approach is aligned with design science research for IS (ISDSR) paradigm (Simon 1996;Hevner et al 2004;Fischer et al 2010) which has been applied to multiple areas of IS design to date (Heinrich and Schwabe 2017;Simon 2010;Oberle et al 2009;Bitzer et al 2015). The following paragraphs briefly explain how seven guidelines of ISDSR methodology map to various tasks/activities of current research.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, the listed requirements make clear that designing a system for use in advisory services is a challenge. Simultaneously, research (Dolata & Schwabe, 2016b, 2017bHeinrich & Schwabe, 2018;Nussbaumer et al, 2012) and politics (Oehler et al, 2010;Oehler & Kohlert, 2009) call for a more effective information transfer and higher transparency in advisory services, such that the advisor and the advisee can engage in collaborative problem-solving. IT can play a major role in this regard.…”
Section: Technology In Advisory Servicesmentioning
confidence: 99%
“…IT can play a major role in this regard. Previous research on supporting financial advice has shown that dynamic manipulation of data can support client education, such that advisees can make more informed decisions and acquire an understanding of the core issues under consideration Heinrich & Schwabe, 2018). It can also contribute towards informational and procedural transparency (Nussbaumer et al, 2012) and help the client share relevant information in a more structured and complete way (Kilic, 2018;Kilic et al, 2015).…”
Section: Technology In Advisory Servicesmentioning
confidence: 99%
See 1 more Smart Citation